ANALISIS PENGARUH PERGESERAN LUBANG PENAMPANG KOLOM BETON BERTULANG PERSEGI BERLUBANG - Rendi Nopradego; Mukhlis Islam (Universitas Bengkulu, 2019)
This Research is based on the difficulty of implementation of the hole installation centered in the middle column. The influence of shifting the hole to column capacity reduction occurs when the hole is shifted towards to the compression area. This study analizes the effect of shifting the hole in rectangular reinforced concrete column against capacity of the column structure decrease. This calculation consists of 144 samples with different compression strength (fc’),reinforcements area, hole area, and dimensions of the column. The analysis is based on the assumption of linear strain distribution in cross section with appropriate stress-strain correlation using Hognestaad equation. Reinforced concrete structural element were analyzedonly experiencing a combination of uniaxial bending moment. The results of the analysis effect of shifting the hollow in rectangular reinforced concrete column decreased capacity of the colomn. The largest decline of the column capacity occured on 100% the shift column holesfrom the hole centered in the middle column on dimension of 600 mm x 600 mm with fc' 30 MPa, reinforcement quality (fy) 400 MPa, reinforcement extensive of 1%, and holes extensive of 7% is 10.38% of axial forces (Pn) and 9.06% of Nominal Moment (Mn). The effect of shifting the hole towards to the compression area is affecting the capacity of hollow in rectangular reinforced concrete column centric decreasing.